Hydrogen-bonded supramolecular polymer micelles with pH/photothermal-responsive carmofur release and combined chemo-photothermal therapy. Issue 8 (7th February 2022) - Wu, Yanggui; Wang, Huiying; Liu, Qianqian; Lortie, Frédéric; Bernard, Julien; Binder, Wolfgang H.; Chen, Senbin; Zhu, Jintao
Abstract : This work targets the construction of hydrogen-bonded (H-bonded) supramolecular polymeric micelles loaded with chemotherapy drugs (carmofur) and photothermal agents (IR780) for combined chemo-photothermal therapies (CT/PTT). Abstract : Integrating biomedical applications ( e.g., drug delivery) into supramolecular chemistry is a promising strategy. This work targets the construction of hydrogen-bonded (H-bonded) supramolecular polymeric micelles loaded with chemotherapy drugs (carmofur) and photothermal agents (IR780) for combined chemo-photothermal therapies (CT/PTT).